Impact of a Family-Based Educational Intervention on Knowledge, Attitudes, and Burden of Alzheimer's Caregivers - Amal Ibrahim Khalil, Neama Yousef Hantira, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Family caregivers always encounter high levels of psychological distress and physical strain when caring for a person with dementia. Family-based intervention is an important option for providing effective and practical support. The study aimed to examine the effects of a specific educational intervention on improving Alzheimer's caregivers' knowledge and attitudes and explore how it reduces their subjective burdens. Material and Methods: A quasi-experimental research design was used with a purposive sample of 80 Alzheimer caregivers recruited conveniently from the Geriatric Society Association located at Almontazahat District, Jeddah, Saudi Arabia. To achieve the objectives of the current study 4 tools were used including demographic and personal data, Alzheimer's Disease Knowledge Scale (ADKS), The Dementia Attitudes Scale, and the burden scale of caregivers. Validity and reliability of the tools were confirmed and Cronbach's alpha of the Dementia Attitudes Scale was 0.87 and Cronbach's alpha of the burden scale of caregivers 0.941. Results: the age of the studied subjects ranged from 20 to 60 years with a mean of 35.6±12.2 years. the studied subject's knowledge level and attitudes were improved post-intervention than before. These differences were statistically significant (t: 108.008, P:<0.001). While, the studied subject's disease burden level was decreased post-intervention than before These differences were statistically significant (t: 8.378, P:<0.001). There is a weak positive significant relation between the studied subject's knowledge level and attitude regarding dementia (r:0.286, P:0.010). Whereas there is no correlation noted between knowledge level and caregiver burden with no statistical significance (r: -.048, P: 0.674). Conclusion and recommendation: the findings concluded that the studied subject's knowledge, attitude, and burden level were improved post-intervention than before with statistically significant differences. Therefore, it is recommended to develop a well-planned and structured educational program should be undertaken to improve the level of awareness and contribute to a better understanding of AD and dementia.